2009
DOI: 10.1159/000215727
|View full text |Cite
|
Sign up to set email alerts
|

Apolipoprotein E, CI and B Gene Polymorphisms in a Sample of Patients with Coronary Heart Disease in the Kuwaiti Population

Abstract: Objectives: The objective of this study was to investigate the possible association of clinical variables and apolipoprotein (APOE, APOCI and APOB) polymorphisms with the development of myocardial infraction (MI) and coronary heart disease (CHD) in Kuwaitis. Subjects and Methods: APOE, APOCI and APOB genotypes were determined by polymerase chain reaction followed by restriction fragment length polymorphism in 143 Kuwaiti CHD patients with (n = 88) and without (n = 55) MI and in 122 controls matched for gender … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 47 publications
0
11
0
Order By: Relevance
“…All studies indicated that the distribution of genotypes in the controls was consistent with HWE, except for 7 studies [29, 35, 37, 39, 40, 45, 46] ( P < 0.05). According to the quality criteria, there were 21 studies with high quality (NOS score > 6).…”
Section: Resultsmentioning
confidence: 98%
“…All studies indicated that the distribution of genotypes in the controls was consistent with HWE, except for 7 studies [29, 35, 37, 39, 40, 45, 46] ( P < 0.05). According to the quality criteria, there were 21 studies with high quality (NOS score > 6).…”
Section: Resultsmentioning
confidence: 98%
“…Based on the search strategy, 571 potentially eligible studies were identified in the initial search. Among these, 22 studies were enrolled in this meta-analysis based on the inclusion criteria [11] , [12] , [13] , [14] , [15] , [16] , [17] , [18] , [19] , [20] , [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] ( Fig. 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, further studies are warranted among Asian populations. In addition, genotype distributions in the controls from Scaglione’s study [28], Bustan’s study [49] and Zende’s study [52] were not in agreement with HWE, therefore, the results may be biased. However, sensitivity analysis suggested that the pooled results were not significantly changed after excluding the three studies (data not shown).…”
Section: Discussionmentioning
confidence: 99%